Drosophila odorant receptors are both ligand-gated and cyclic-nucleotide-activated cation channels. - Wicher, D.; Schäfer, R.; Bauernfeind, R.; Stensmyr, M.C.; Heller, R.; Heinemann, S.H.; Hansson, B.S. (Nature, 2008)
From worm to man, many odorant signals are perceived by the binding of volatile ligands to odorant receptors that belong to the G-protein-coupled receptor (GPCR) family. They couple to heterotrimeric G-proteins, most of which induce cAMP production. This second messenger then activates cyclic-nucleotide-gated ion channels to depolarize the olfactory receptor neuron, thus providing a signal for further neuronal processing. Recent findings, however, have challenged this concept of odorant signal transduction in insects, because their odorant receptors, which lack any sequence similarity to other GPCRs, are composed of conventional odorant receptors (for example, Or22a), dimerized with a ubiquitously expressed chaperone protein, such as Or83b in Drosophila. Or83b has a structure akin to GPCRs, but has an inverted orientation in the plasma membrane. However, G proteins are expressed in insect olfactory receptor neurons, and olfactory perception is modified by mutations affecting the cAMP transduction pathway. Here we show that application of odorants to mammalian cells co-expressing Or22a and Or83b results in non-selective cation currents activated by means of an ionotropic and a metabotropic pathway, and a subsequent increase in the intracellular Ca(2+) concentration. Expression of Or83b alone leads to functional ion channels not directly responding to odorants, but being directly activated by intracellular cAMP or cGMP. Insect odorant receptors thus form ligand-gated channels as well as complexes of odorant-sensing units and cyclic-nucleotide-activated non-selective cation channels. Thereby, they provide rapid and transient as well as sensitive and prolonged odorant signalling.